2015
DOI: 10.14202/vetworld.2015.478-481
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of antibiotic resistant Staphylococcus aureus from raw milk samples collected from the local vendors in the region of Tirupathi, India

Abstract: Aim:The study was carried out with the aim to identify the suitability of the milk for consumer use with special reference to Staphylococcus aureus from milk samples collected from various local vendors and determine the antibiotic susceptibility pattern of those positive isolates.Materials and Methods:A total of 110 milk samples were collected from the local milk vendors in and around Tirupathi region of India. All the samples were enriched with buffered peptone water in 9:1 ratio and the then inoculated on b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
17
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 22 publications
8
17
4
Order By: Relevance
“…Contamination levels were highest in milk cake/khoa (26.0%, 8/30, p = 0.0002) followed by ice cream/kulfi (10.0%, 3/30, p = 0.4), mutton momo (10.0%, 3/30, p = 0.4), burfi (3.3%, 1/30, p = 0.7) and chicken momo (3.3%, 1/30, p = 0.7) ( Table 2). Our findings are in agreement with previous studies conducted in Italy (milk and dairy products), Turkey (raw milk and dairy products) and India (Carfora et al 2015;Gundogan and Avci 2014;Sudhanthiramani et al 2015). The presence of S. aureus in food indicates adoption of poor hygienic measures from production to consumption of food (Fleurot et al 2014).…”
Section: Resultssupporting
confidence: 92%
“…Contamination levels were highest in milk cake/khoa (26.0%, 8/30, p = 0.0002) followed by ice cream/kulfi (10.0%, 3/30, p = 0.4), mutton momo (10.0%, 3/30, p = 0.4), burfi (3.3%, 1/30, p = 0.7) and chicken momo (3.3%, 1/30, p = 0.7) ( Table 2). Our findings are in agreement with previous studies conducted in Italy (milk and dairy products), Turkey (raw milk and dairy products) and India (Carfora et al 2015;Gundogan and Avci 2014;Sudhanthiramani et al 2015). The presence of S. aureus in food indicates adoption of poor hygienic measures from production to consumption of food (Fleurot et al 2014).…”
Section: Resultssupporting
confidence: 92%
“…The molecular confirmation of S. aureus isolates with nuc gene (Thermonuclease) amplified a 188 bp specific amplicon product. Sudhanthiramani et al (2015) reported that prevalence of 39.09% (43/110) coagulase-positive S. aureus from the milk samples which is in accordance with our study, whereas Bhati et al (2018) reported 107/197 (54.31%) S. aureus isolates confirmed from mastitic milk samples, udder and milkers' hands by 23s rRNA based PCR in Rajasthan, India. Akriti et al (2019) documents the prevalence of S. aureus as 66.66% (40/60) in the cattle milk samples collected from Vallabhnagar tehsil of Udaipur district.…”
Section: Resultssupporting
confidence: 89%
“…Besides the antibiogram test, the PCR amplification result indicated that all antimicrobial tested CoPS isolates carried the fem A gene and among these isolates, 12 (37.5%) carried mec A gene (MRSA). This finding was in line with the findings of authors [70] [38], who reported 86.04% resistance to Penicillin G and 74.42% to Ampicillin [45], who reported 100% resistance to Penicillin G and 46.8% to Oxacillin, and 44.6% to vancomycin, detected mec A by polymerase chain reaction in 4 of the 18 MRSA isolates, and 88.9% multi-drug resistance [46], who reported 100% of resistance to Penicillin G, 65% to Amoxicillin, and 40% to Oxacillin [56], who reported 98.5% resistance to Penicillin G [55], who reported 95.3% resistance to Penicillin G, and 100% of multidrug resistance, and [52] who reported 95.5% resistance to Penicillin G and 95.5% of multidrug resistance. However, the current finding of MRSA was higher than the reports of [66] (8.93%) [38], (13.95%) [47], (8.3%) [45], (4.8%), and [73] (5.9%).…”
Section: Discussionsupporting
confidence: 93%
“…The present study revealed that 39.1% (111/284) of the overall prevalence of CoPS and of these 111 isolates, 51(56.04%), 38(26.20%) and 22(45.83%) were isolated from meat, raw milk and yogurt, respectively. This overall prevalence of CoPS was nearly comparable with the findings of studies conducted [36] in Asella, South Eastern Ethiopia (35.71%) [17], in Northen Ethiopia (36%) [37], in and around Wolaita Sodo, Southern Ethiopia (37.14%) [38], in the region of Tirupathi, India (39.09%) [39], in Adama town, Ethiopia (42.14%), and [40] in Urban and peri-urban areas of Debre-Zeit, Ethiopia (44%). However, the present finding was higher than the reports [41] in Addis Ababa, Ethiopia (9%) [42], (9.1%) [43], in Addis Ababa, Ethiopia (10%) [16], in selected Districts of Tigray (9.8%) [44], in Mityana District, Uganda (10%) [45], in Zaria and Kaduna, Nigeria (12.6%) [46], in Nigeria (12.63%) [47], in South Italy (12.9%) [48], around Addis Ababa, Ethiopia (16.2%) [49], in Fars, Chahar Mahalva Bakhtiari and Ghom, provinces, Iran (17.9%) [50] [45], in Zaria and Kaduna, Nigeria (52.42%), and [69] in Hawassa town, Ethiopia (53.5%).…”
Section: Discussionsupporting
confidence: 87%